Factors influencing quality of life in adolescents with type 1 diabetes mellitus: A cross-sectional study in South Korea - Park, Hye-Ryeon; Park, So-Yeon (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: The promotion of quality of life for adolescents with type 1 diabetes mellitus enables them to achieve physical, psychological, and social development. Improving quality of life positively influences their well-being in adulthood. Objective: This study aimed to identify the factors influencing quality of life in adolescents with type 1 diabetes mellitus. Methods: Data were collected from April 2022 to February 2023. The quality of life of 146 adolescents with type 1 diabetes mellitus was analyzed. The data were analyzed using IBM SPSS Statistics 25.0, with t-tests, ANOVA, Pearson’s correlation, and stepwise multiple regression. Results: The quality of life of adolescents with type 1 diabetes was significantly correlated with depression (r = -0.31, p <0.001) and diabetes distress (r = -0.42, p <0.001). Stepwise multiple regression analysis identified diabetes distress (β = -0.38, p <0.001) and insulin treatment (β = 0.15, p = 0.048) as factors influencing quality of life. Conclusion: Periodic education and nursing interventions to improve self-care capacity for adolescents with type 1 diabetes mellitus are essential for reducing diabetes distress. Additionally, it is important to promote the use of insulin pump at the national level, include expanding insurance coverage and offering personalized insulin pump education.